Asked by  | 13th Feb, 2009, 10:28: PM

Expert Answer:

The sum of the zeroes of a polynomial  in x =-b/a


 the product of the zeroes=c/a


 a is coefficient of x squared and b is coefficient of the  term in x and c is the term free of x.

So, here,

a=1, b=-8 and c=k

So sum of the zeroes = -b/a= -(-8)/1=8

product of the zeroes=c/a=k

We need to find the sum of squares of the zeroes.

Answered by  | 14th Feb, 2009, 08:46: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.